MANAJEMEN PROGRAM LATIHAN MODIFIKASI PENINGKATAN KUALITAS GERAK DAN KEMAMPUAN RENANG PENDERITA SKOLIOSIS DI LES RENANG PALU - Safana, Ajriana; didik, Didik Purwanto; Andi Saparia; Agung prasetyo, Rahmad; Maria Tolok, Ina Nogi (Fakultas Ilmu Keolahragaan Unimed, 2026)
This study aims to analyze the urgency and elaborate on the implementation of an adaptive swimming exercise program as a non-medical therapy option for scoliosis patients. Scoliosis, a curvature abnormality of the spine, requires comprehensive management, and swimming is often recommended due to its low-impact nature and its ability to strengthen core muscles. The method used is a descriptive case study focusing on a single subject, Emanuel Teddy (13 years old), a scoliosis patient undergoing therapy at Les Renang Palu since February 2024. The applied swimming program was the result of a doctor's recommendation and a needs analysis by the coach, subsequently modified by combining the breaststroke arm movements with the freestyle leg movements. The findings indicate that through routine and disciplined swimming therapy, the subject's core and back muscle strength condition improved, which is a positive indication in managing scoliosis